Identification of Endoparasites in Javan Banteng (Bos javanicus javanicus) in Ujung Kulon National Park (UKNP) - Handayani; Marini Agustin; Arifin Budiman Nugraha; Tiara Primayanti (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Research on parasitic infections in the Javan rhinoceros (Rhinoceros sondaicus) and banteng (Bos javanicus javanicus) in Ujung Kulon National Park has been reported before. This study not only identifies the types of endoparasites but also measures the infection levels using eggs per gram of feces (EPG) and oocysts per gram of feces (OPG). This research aims to determine the impact of endoparasite infection on the health of the banteng (Bos javanicus javanicus) in its natural habitat at Ujung Kulon National Park (UKNP), through identifying the types of endoparasites that infect, prevalence analysis, and the level of infection. The sample identification was carried out at the Protozoology Laboratory of the Faculty of Veterinary Medicine and Biomedical Sciences of Institut Pertanian Bogor (IPB) University. Identification process using the flotation method, sedimentation method, native method, and the McMaster.The results of this research found five types of parasite eggs: Ascarid, Strongyloides, strongyloid, Paramphistomum, and Eimeria. The infection levels of each parasite, based on the calculation of eggs per gram of feces (EPG) and oocysts per gram (OPG), are as follows: ascarid at 1,050 EPG, Strongyloides at 1,600 EPG, Strongloides at 1,600 EPG, Paramphistomum at 50 EPG, and Eimeria at 550 OPG.